2017
DOI: 10.1002/ijc.30793
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adjuvant therapy for node‐positive clinical stage IB‐IIB cervical cancer: Systemic chemotherapy versus pelvic irradiation

Abstract: This was a nation-wide retrospective study in Japan examining women who underwent radical hysterectomy for clinical stage IB-IIB cervical cancer with pelvic and/or para-aortic lymph node metastasis between 2004 and 2008. Time to recurrence or death and patterns of disease recurrence were compared based upon the adjuvant treatment pattern: whole pelvic radiotherapy alone (n = 253), concurrent chemoradiotherapy (CCRT, n = 502) and chemotherapy alone (n = 319). Women who received chemotherapy alone had similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
2
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 40 publications
1
77
2
2
Order By: Relevance
“…The current study validates the results of prior studies in that the presence of malignant cells in pelvic cytology testing at the time of radical hysterectomy is associated with decreased survival in women with early-stage cervical cancer. As prior studies were limited in the sample size (range, 105-448) and the number of malignant peritoneal cytology cases (range, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], the findings from our study, which included a larger patient pool, are more reliable for interpretation of the analysis [6][7][8][9][10].…”
Section: Prognostic Significancementioning
confidence: 82%
See 3 more Smart Citations
“…The current study validates the results of prior studies in that the presence of malignant cells in pelvic cytology testing at the time of radical hysterectomy is associated with decreased survival in women with early-stage cervical cancer. As prior studies were limited in the sample size (range, 105-448) and the number of malignant peritoneal cytology cases (range, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], the findings from our study, which included a larger patient pool, are more reliable for interpretation of the analysis [6][7][8][9][10].…”
Section: Prognostic Significancementioning
confidence: 82%
“…This is a secondary analysis of a prior nationwide multicenter retrospective study conducted in Japanese Gynecologic Oncology Group (JGOG)-designated institutions [18][19][20][21][22][23][24][25]. The study concept and participation call for this landmark collaborator study was initially announced to all JGOG-designated institutions (182 sites), and 116 (63.7%) of these sites voluntarily participated in this study (JGOG-1072S).…”
Section: Data Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Several retrospective studies on postoperative adjuvant CT alone have also been reported and all of them conclude that systemic CT alone as postoperative adjuvant therapy could obtain similar or better results compared with RT/CCRT. [18][19][20][21] Matsuo et al 22 In summary, adjuvant CT alone with TN after radical hysterectomy for patients with high-risk early-stage cervical cancer was demonstrated to be an effective and feasible treatment. We suggest that a prospective randomized study be conducted with the aim of testing the noninferiority of systemic CT alone to CCRT as optimal adjuvant therapy for patients with factors placing them at high risk for recurrence.…”
Section: Discussionmentioning
confidence: 99%